Typical Academic Electronic Library Creation - Babenko, B.O.; Babina, T.B.; Volinets, B.M.; Gabzovska О.Б.; Druchenko М.Л.; Savitsky А.Й. (Journal of Information Technologies in Education (ITE), 2009)
In article results of G.I.Denisenko NTUU “KPI” NTL information funds structure analysis were presented in the context of topical collection of documents, readership category, documents types. Level of academy library acquisition was determined. Analysis results are base for determine of top-priority guidelines digitization published editions providing. This is basis for academic electronic library collections.